PROBLEMS IN TEACHING ARABIC IN INDIA WITH SPECIAL REFERENCE TO JAMIA MILLIA ISLAMIA - Nadwi, Mohammad Ayub (State Islamic University North Sumatra, 2022)
Abstract: The contribution of India in the development of the Arabic language has been realized since a long time ago and it has a long history because of Urdu language has become a small part of the Arabic language besides that the cultures and civilizations that exist in India have something in common. Likewise, the establishment of Islamic and general education centers that pay attention to learning Arabic shows that there is a close historical relationship with this country. This paper describes some of the conditions for the development of Arabic language learning at the Jamia Millia Islamic University-New Delhi India using library research methods and evidence obtained in the field to support them.Keywords: Arabic Language, Jamia Millia Islamic University, India and Learning